Introduction to research in education - Ary, Donald; Jacobs, Lucy Cheser; Sorensen, Christine Knupp; Walker, David A. (Boston, MA : Cengage, 2019)
Helps students master the basic competencies necessary to understand and evaluate the research of others, and shows them how to plan and conduct original research. This book builds on the text's strengths of teaching students to become more competent consumers and producers of research.
1. The nature of research in education -- 2. The research problem -- 3. Reviewing the literature -- 4. Ethics in educational research -- 5. Measurement -- 6. Validity and reliability -- 7. Descriptive statistics -- 8. Sampling and inferential statistics -- 9. Experimental research -- 10. Experimental research designs -- 11. Ex post facto research -- 12. Correlational research -- 13. Survey Research -- 14. Interpreting and reporting results of quantitative research -- 15. Defining and designing qualitative research -- 16. Types of qualitative research -- 17. Data-collection tools in qualitative research -- 18. Rigor and ethics in qualitative research -- 19. Analyzing and reporting qualitative research -- 20. Action research -- 21. Mixed methods research.
Previous edition: 2014.
Includes bibliographical references and index.
Keywords: Education -- Research